Assessment of Mandibular Fractures by Multislice Computed Tomography and Reconstructed Three Dimensional Computed Tomography - Zeinab A. Mustafa; Doria S. Salem; Mary M. Farid; Farid M. Farid; Durer F. Iskanderani (Journal of King Abdulaziz University: Medical Sciences, 2023)
Panoramic radiography was the common technique in assessment of mandibular fractures. It is two dimensional and has a significant magnification that limit an accurate interpretation of images associated with traumatically injured mandible. The objective of this study was to assess the mandibular fractures by multislice computed tomography and reconstructed three-dimensional computed tomography. This study involved five Egyptian patients of different ages and sexes. All patients were complaining of traumatic facial injuries. They were subjected to clinical and radiological examinations, which they were submitted to panoramic radiography as well as multislice computed tomography with three dimensional reconstructions. It was found that multislice computed tomography and reconstructed three dimensional computed tomography images are more reliable in detecting and revealing many missed mandibular fractured fragments that are not seen on conventional radiography. This concludes that the combination of multislice computed tomography and reconstructed three dimensional computed tomography allowed several improvements and changes in the treatment plane, as well as operative management of mandibular fractures.